PREVALENCE OF POLYMORPHOUS LOCUS 681G>A OF CYP2C19 GENE IN RUSSIAN POPULATION - T. A. Bairova; S. A. Churbanova; S. I. Kovesnikov; O. V. Kalyuzhnaya (Acta Biomedica Scientifica, 2014)
The prevalence of genotypes and alleles of polymorphous locus 681G>A of CYP2C19 gene in Russian population of Eastern Siberia. We conducted comparative analysis of response characteristics with previous data of other world's populations. Genotyping was conducted using PCR method. Statistical processing was performed using «Hardy - Weinberg equilibrium calculator» and STATISTICA 8.0. Significant differences of prevalence of alleles of studied polymorphous locus between researched population and data of other researchers were discovered.